2018
DOI: 10.1177/0017896918786017
|View full text |Cite
|
Sign up to set email alerts
|

Little lifesavers: Can we start first aid education in kindergarten? – A longitudinal cohort study

Abstract: Objectives: First aid programmes should include not only the transfer of knowledge and skills but also improve participants’ helping attitudes. The aim of this study was to evalute the immediate and long-term effects of a 3-day first aid programme for kindergarten children. Methods: One hundred and eighteen kindergarten children (5–7 years old) from an inner-city kindergarten located in Pécs, Hungary, were involved in this study between January 2016 and June 2017. Training consisted of three 45-minute sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
(31 reference statements)
2
27
0
Order By: Relevance
“…Also, 60% showed a correct breathing assessment, and 40% of the participants accomplished the other tasks (giving correct emergency call information, knowledge of correct recovery position, correct airway management) correctly [10]. Also, the research by Bánfai showed the same results [23].…”
Section: Discussionmentioning
confidence: 69%
“…Also, 60% showed a correct breathing assessment, and 40% of the participants accomplished the other tasks (giving correct emergency call information, knowledge of correct recovery position, correct airway management) correctly [10]. Also, the research by Bánfai showed the same results [23].…”
Section: Discussionmentioning
confidence: 69%
“…A meta-analysis concluded that children and young people are able to reliably learn and deliver first aid (He, Wynn, and Kendrick 2014). Bánfai et al (2018) evaluated 118 Hungarian 5 to 7-year-olds, who were trained in first aid and tested immediately after the training, and again after four and 15 months. The children's knowledge of first aid techniques improved significantly after the training, although there was a considerable dip in children's knowledge over time.…”
Section: Children's First Aid Skillsmentioning
confidence: 99%
“…On the other hand, these results could also have been influenced by the fact that the students did not internalize, during the training, the feedback received from the mannequin, which clearly showed the depth of compression performed by the participants [ 44 ]. Despite limitations in percentage of correct depth, it has been shown that students can learn to check scene safety, check for consciousness, assess breathing, call the emergency number, or position their hands correctly during CPR [ 4 ], a set of actions that can be very valuable in a real emergency [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, in developed countries, immediate resuscitation and early bystander defibrillation are the weakest links in the chain of survival [ 3 ]. Therefore, BLS education in early childhood may be key to increasing the effective number of bystanders providing cardiopulmonary resuscitation (CPR) and early defibrillation [ 4 ]. In this sense, the World Health Organization (WHO), in agreement with international organizations such as the American Heart Association [ 5 ] and the European Resuscitation Council (ERC) [ 6 ], recommend initiatives to increase basic CPR by witnesses, which should be taught to all citizens, including schoolchildren, through the so-called “Helping Hands-Training children is training for life” [ 7 ].…”
Section: Introductionmentioning
confidence: 99%